Analisis Pengaruh Electronic Word of Mouth (EWOM) dalam Mempengaruhi Keputusan Berkunjung ke Dinoland Garut - Taofik Hidayat; Andi Muhammad Rudhan; Lisna Rindiani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Rapid developments in digital technology have made information about tourist destinations more accessible to the public, one of which is through Electronic Word of Mouth (EWOM). This study aims to analyse the influence of EWOM on the decision to visit Dinoland Garut. This study uses a quantitative approach with descriptive and associative methods. The population in this study was visitors to Dinoland Garut, with sampling techniques using incidental non-probability sampling. The number of samples used was 68 respondents, selected based on specific criteria. Data was collected through questionnaires distributed directly to visitors who had visited Dinoland. The results showed that there was a significant influence between EWOM and the decision to visit. Good information management through digital platforms can increase visitor interest, thereby increasing the decision to visit. The implication of this study is that tourism destination managers need to utilise EWOM as a marketing strategy to increase the number of visitors and improve the image of tourism destinations in the public eye.